2016
DOI: 10.5021/ad.2016.28.6.749
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Pictures of Kaposi's Sarcoma in Psoriatic Lesions: A Diagnostic Challenge

Abstract: Kaposi's sarcoma is a multifocal proliferative vascular tumor involving the skin and other organ and psoriasis is a chronic cutaneous disease with papules and plaques with white scale. Development of Kaposi's sarcoma in psoriasis patients has been reported rarely. A 71-year-old man presented with multiple brownish to violaceous plaques on both feet and arms which were found 4 months ago. The biopsy confirmed Kaposi's sarcoma. The patient was diagnosed with psoriasis vulgaris 10 years ago and Kaposi's sarcoma l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It has recently been revealed that a subclass of this disorder is linked to KS-associated herpesvirus (KSHV), in which KSHV infection can be found in almost all HIV-associated cases of MCD and 50% of HIV-negative patients ( 4 ). Several scholars have mentioned the concurrence of KS and psoriasis, which presents a diagnostic challenge due to the resemblance between the lesions of both conditions ( 15 , 16 ). Furthermore, another epidemiological study revealed a high risk of KS in patients with psoriasis ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been revealed that a subclass of this disorder is linked to KS-associated herpesvirus (KSHV), in which KSHV infection can be found in almost all HIV-associated cases of MCD and 50% of HIV-negative patients ( 4 ). Several scholars have mentioned the concurrence of KS and psoriasis, which presents a diagnostic challenge due to the resemblance between the lesions of both conditions ( 15 , 16 ). Furthermore, another epidemiological study revealed a high risk of KS in patients with psoriasis ( 17 ).…”
Section: Discussionmentioning
confidence: 99%